Risk and rationality: The effect of incidental mood on probability weighting - Helga Fehr; Thomas Epper; Adrian Bruhin; Renate Schubert (University of Zurich, Socioeconomic Institute, 2007)
When valuing risky prospects, people tend to overweight small probabilities and to underweight large probabilities. Nonlinear probability weighting has proven to be a robust empirical phenomenon and has been integrated in decision models, such as cumulative prospect theory. Based on a laboratory experiment with real monetary incentives, we show that incidental emotional states, such as preexisting good mood, have a significant effect on the shape of the probability weighting function, albeit only for women. Women in a better than normal mood tend to exhibit mood-congruent behavior, i.e. they weight probabilities of gains and losses relatively more optimistically. Men's probability weights are not responsive to mood state. We find that the application of a mechanical decision criterion, such as the maximization of expected value, immunizes men against effects of incidental emotions. 40% of the male participants indeed report applying expected values as decision criterion. Only a negligible number of women do so.
Keywords: 330; Risikopräferenz; Männer; Frauen; Statistische Methode; Test; Schätzung